Optimizing and forecasting the development of China’s sports industry structure - Fanxiang Zhao; Hongjian Gao (PLoS ONE, 2025)
The sports industry’s contribution to economic growth is increasingly pronounced, as structural optimization offers significant potential to enhance its impact on economic development. This study employs the grey relational analysis and GM (1,1) grey prediction models to examine the correlation between China’s sports sub-sectors and key national economic development indicators, providing projections for future trends. Results indicate that the sports manufacturing sector and related product sales demonstrate the strongest correlation with Gross Domestic Product (GDP), highlighting their critical role in fostering economic growth. The GM (1,1) model reliably forecasts future trends in the sports industry’s added value. Based on these insights, sector-specific recommendations are proposed to promote structural optimization and sustainable development in China’s sports industry.